IMPLEMENTATION OF RISK-BASED LICENSING IN THE MARINE AND FISHERIES SECTOR POST THE APPLICATION OF THE EMPLOYMENT CREATION LAW - Abdillah, Dani (Universitas Ekasakti, 2023)
Indonesia has abundant marine and fishery economic potential that can be managed and utilized for the welfare of the people and increase national economic growth, and potentially almost three quarters of the territory of the Republic of Indonesia is the ocean with all the sources of wealth contained therein. Nawacita Program His government said that Indonesia has the potential to become the world's maritime axis and the sea is the future of the nation towards a golden Indonesia 2045, to guard President Jokowi Nawacita world maritime axis, it is translated into 3 (three) missions, namely, first, Sovereignty, namely being independent in managing and utilizing marine resources. and fisheries by strengthening national capacity to enforce law at sea in order to realize economic sovereignty, secondly, Sustainability. Adopting the blue economy concept in managing and protecting marine and fishery resources responsibly with environmentally friendly principles as an effort to increase productivity, which is carried out through marine space management; management of marine biodiversity, three. Welfare namely managing marine and fishery resources is for the greatest prosperity of the people, which is carried out through human resource capacity development and community empowerment; and development of marine and fisheries science and technology innovations. As mentioned above, the independence of fisheries resource management is how the government enforces the law at sea even though the government has previously issued Law Number 31 of 2004 As amended by Law Number 45 of 2009 concerning Amendments to Law Number 31 concerning Fisheries which is a law enforcement regulation in the marine and fisheries sector which over time in 2020, the House of Representatives and the Government have issued and ratified Law Number 11 of 2020 concerning Job Creation which with the issuance of the Job Creation Act, there are several articles in the Law. -Law Number 31 of 2004 As amended by Law Number 45 of 2009 concerning Amendments to Law Number 31 concerning Fisheries, several changes have been made as well as in the Law on Marine and Fisheries Job Creation, ah sector whose management and utilization requires having a Business Licensing Risk Base Approach.